2017
DOI: 10.1038/s41598-017-07699-3
|View full text |Cite|
|
Sign up to set email alerts
|

Magnesium Oxide (MgO) pH-sensitive Sensing Membrane in Electrolyte-Insulator-Semiconductor Structures with CF4 Plasma Treatment

Abstract: Magnesium oxide (MgO) sensing membranes in pH-sensitive electrolyte-insulator-semiconductor structures were fabricated on silicon substrate. To optimize the sensing capability of the membrane, CF4 plasma was incorporated to improve the material quality of MgO films. Multiple material analyses including FESEM, XRD, AFM, and SIMS indicate that plasma treatment might enhance the crystallization and increase the grain size. Therefore, the sensing behaviors in terms of sensitivity, linearity, hysteresis effects, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The change in the reference voltage might occur from lattice defects, which co for example, vacancies or dangling bonds caused by capturing groups of ions. The fects might be eliminated by controlling the parameters of the preparation method for the sensing membranes, such as the annealing temperature [15,27,73] and the d process [33,67], which result in the improvement of the drift voltage over time. In to study the long-term stability (drift) of the sensing membranes, each sample wa merged in a solution of pH 7 for 12 h. Figure 10 presents the drift rates of the EIS d based on Mg-doped ZnO nanorod sensing membranes doped at different contents ( Figure 10 shows that, among the samples doped with Mg, the EIS device with the 3 ZnO membrane exhibited the highest stability (0.218 mV/h), whereas the 2% M membrane had the lowest stability of 0.659 mV/h.…”
Section: The Undoped Zno and Mg-doped Zno Nanorod Sensing Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The change in the reference voltage might occur from lattice defects, which co for example, vacancies or dangling bonds caused by capturing groups of ions. The fects might be eliminated by controlling the parameters of the preparation method for the sensing membranes, such as the annealing temperature [15,27,73] and the d process [33,67], which result in the improvement of the drift voltage over time. In to study the long-term stability (drift) of the sensing membranes, each sample wa merged in a solution of pH 7 for 12 h. Figure 10 presents the drift rates of the EIS d based on Mg-doped ZnO nanorod sensing membranes doped at different contents ( Figure 10 shows that, among the samples doped with Mg, the EIS device with the 3 ZnO membrane exhibited the highest stability (0.218 mV/h), whereas the 2% M membrane had the lowest stability of 0.659 mV/h.…”
Section: The Undoped Zno and Mg-doped Zno Nanorod Sensing Performancementioning
confidence: 99%
“…EIS sensors have been developed in different biosensing applications in the environmental and pharmaceutical environments [9][10][11]. Several sensing metal oxide films are used for pH sensing applications, such as IGZO, ITO, Ta 2 O 5 , MgO, Al 2 O 3 /SiO 2 , TiO 2 , CuO, and ZnO [12][13][14][15][16][17][18][19]. The flat-band voltage of the EIS device changes depending on the ionic conditions of the tested solution.…”
Section: Introductionmentioning
confidence: 99%
“…To further enhance ion-sensing capabilities, it is worthwhile to explore materials, alternative fabrication processes, and treatments such as addition of nanoparticles or modulation of the membrane thickness [ 8 , 9 ]. In addition, incorporating post treatments such as Magnesium (Mg) doping and ammonia (NH 3 ) plasma treatment may optimize the membrane performance [ 7 , 10 , 11 ]. In this study, InGaZnO films, which can function as a transparent conductive oxide, have been demonstrated as ion-sensing membranes in electrolyte-insulator-semiconductor (EIS) structures.…”
Section: Introductionmentioning
confidence: 99%
“…Note, that properties of nanowires, or nanorods, and slabs have attracted interest 9 due to applications in field emission devices 10 and sensing. 11 Early studies of nanoclusters typically reported the tentative global energy minimum atomic configuration of a compound as a function of the number of formula units, n, it is composed of. The structural motif of these global minima for a compound will also typically change with size n; the smallest global minima may not resemble cuts that can be taken from the crystal structure of the bulk phase.…”
Section: Introductionmentioning
confidence: 99%